Mborasei porañetesa = El espíritu de la música (CEFREC, 2016)
The experience of a Guaraya indigenous adolescent and the important experience of artistic formation of the Institute of Integral Chorus and Orchestra formation of Urubichá, allow to visualize the valuable contribution of an education conceived from the new precepts of intraculturality, interculturality and plurilinguism of the current legislative and constitutional framework of Bolivian education. --